A Whole-Brain Cell-Type-Specific Sparse Neuron Labeling Method and Its Application in a Shank3 Autistic Mouse Model - Chen, Di; Ren, Keke; Liu, Haiying; Mao, Honghui; Li, Zongyan; Mo, Huiming; Xie, Shengjun; Shi, Yiwu; Chen, Qian; Wang, Wenting (Frontiers in Cellular Neuroscience, 2020)
Single neurons, as the basic unit of the brain, consist of a cell body and processes, including dendrites and axons. Even neurons of the same type show various subtle process characteristics to fit into the diverse neural circuits. Different cell types of neurons form complicated circuits in the brain. Therefore, detailed neuronal morphology is required to understand normal neuronal function and pathological mechanisms, such as those that occur in autism. Here, we developed a strategy to sparsely label the same type of neurons throughout the whole brain and tested its application in an autistic animal model—Shank3 knockout (KO) mice. To achieve this, we designed an adeno-associated virus (AAV) that expresses Cre recombinase-dependent regular and membrane-targeted EGFP under a human synapsin1 promoter and verified it in several Cre transgenic mice. We could sparsely label the projection neurons in multiple brain areas by retro-ocular injection of the virus into CaMKIIα-Cre mice. Then, we analyzed the morphology of the projection neurons in Shank3 KO mice with this method. We found differential dendritic complexity and dendritic spine changes in projection neurons in Shank3 KO mice crossed with CaMKIIα-Cre mice compared with littermate control mice in the striatum, cortex, and hippocampus. By combining this method with various Cre mouse lines crossed with mouse models of disease, we can screen the morphological traits of distinct types of neurons throughout the whole brain that will help us to understand the exact role of the specific cell types of neurons not only in ASD mouse models but also in other psychiatric disorder mouse models.